Pengaruh Kepemimpinan, Motivasi dan Pelatihan terhadap Kinerja Pegawai PT. Bank Rakyat Indonesia (Persero) Kantor Cabang Kendal - Eka Tiara Reza; Lie Liana (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research analyzes the influence of leadership, motivation, and training on team member performance. The population in this study was all PT employees. Bank Rakyat Indonesia (Persero) Kendal Branch Office with 94 respondents. The research method used is quantitative research. Data was collected using a Google form questionnaire with four variables: leadership, motivation, training, and team member performance. Data processing results are in the form of respondent descriptions, variable descriptions, validity test results, reliability test results, F test results, coefficient of determination test results (R2), and hypothesis test results. The results of this study show that leadership does not affect team member performance, motivation has a positive and significant effect on team member performance, and training has a positive and significant impact on team member performance. Conclusion: There is a significant influence between motivation and training on team member performance. However, leadership does not affect team member performance. Keywords: Employee Performance, Leadership, Motivation, Training